Is Overall Mortality the Right Composite Endpoint in Clinical Trials of Acute Respiratory Distress Syndrome?*. Issue 6 (June 2018) - Villar, Jesús; Martínez, Domingo; Mosteiro, Fernando; Ambrós, Alfonso; Añón, José M.; Ferrando, Carlos; Soler, Juan A.; Montiel, Raquel; Vidal, Anxela; Conesa-Cayuela, Luís A.; Blanco, Jesús; Arrojo, Regina; et al.
Abstract : Objectives: Overall mortality in patients with acute respiratory distress syndrome is a composite endpoint because it includes death from multiple causes. In most acute respiratory distress syndrome trials, it is unknown whether reported deaths are due to acute respiratory distress syndrome or the underlying disease, unrelated to the specific intervention tested. We investigated the causes of death after contracting acute respiratory distress syndrome in a large cohort. Design: A secondary analysis from three prospective, multicenter, observational studies. Setting: A network of multidisciplinary ICUs. Patients: We studied 778 patients with moderate-to-severe acute respiratory distress syndrome treated with lung-protective ventilation. Interventions: None. Measurements and Main Results: We examined death in the ICU from individual causes. Overall ICU mortality was 38.8% (95% CI, 35.4–42.3). Causes of acute respiratory distress syndrome modified the risk of death. Twenty-three percent of deaths occurred from refractory hypoxemia due to nonresolving acute respiratory distress syndrome. Most patients died from causes unrelated to acute respiratory distress syndrome: 48.7% of nonsurvivors died from multisystem organ failure, and cancer or brain injury was involved in 37.1% of deaths. When quantifying the true burden of acute respiratory distress syndrome outcome, we identified 506 patients (65.0%) with one or more exclusion criteria for enrollment into current interventional trials. Overall ICU mortality of the "trial cohort" (21.3%) was markedly lower than the parent cohort (relative risk, 0.55; 95% CI, 0.43–0.70; p < 0.000001). Conclusions: Most deaths in acute respiratory distress syndrome patients are not directly related to lung damage but to extrapulmonary multisystem organ failure. It would be challenging to prove that specific lung-directed therapies have an effect on overall survival. Abstract : Supplemental Digital Content is available in the text.